The quorum-sensing regulator ComA from Bacillus subtilis activates transcription using topologically distinct DNA motifs - Wolf, Diana; Rippa, Valentina; Mobarec, Juan Carlos; Sauer, Patricia; Adlung, Lorenz; Kolb, Peter; Bischofs-Pfeifer, Ilka (Nucleic acids research, 2016)
Abstract. ComA-like transcription factors regulate the quorum response in numerous Gram-positive bacteria. ComA proteins belong to the tetrahelical helix-turn-
Published online 17 November 2015
Gesehen am 03.07.2020